Transparencia, acceso a la documentación administrativa y protección de datos de carácter personal - Del Castillo Vázquez, Isabel Cecilia (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2008)
Refusal to any interference in the private life of the individual is found in the genesis of recognition of fundamental right to personal data protection, which offers its holder a power of control over the use of its personal information. Nevertheless, the legitimate exercise of this right does not mean the blockade or the absolute isolation of personal data when its holder decides to deny access, since with the absolute secret neither other fundamental rights are respected, nor the satisfaction of the public interest is met. In such a way, the weighing of constitutionally protected interests will occasionally limit the obliged administrative transparency, with the consequent restriction of access to administrative files. Nevertheless, in other occasions, the prevalence of a more worthy interest of protection will oblige to sacrifice the exercise of the fundamental right to personal data protection. En alemán: Die Entstehung der Anerkennung des Grundrechts auf den Schutz personengebundener Daten ist von ihrem Ursprung an geprägt durch die Zurückweisung des Eingriffs in die Privatsphäre. Jedoch bedeutet die legitime Inanspruchnahme dieses Rechts nicht die Blockade oder die völlige Nicht-Weitergabe der personengebundenen Information (im Falle, dass der Inhaber es so beschließt), da durch die absolute Geheimhaltung andere Grundrechte verletzt warden können bzw. das öffentliche Interesse schaden nehmen könnte. Daher zwingt die Abwägung von verfassungs mässig garantierten Rechten in manchen Fällen dazu, die obligatorische Trans parenz der Verwaltung zu beschränken, mit der Folge, dass der Zugriff auf Verwaltungsarchive eingeschränkt wird. Jedoch kann in anderen Fällen, beim Vorliegen eines schützenswürdigeren Grundrechts, das Recht auf den Schutz personengebundener Daten geopfert werden.